The Impact of Extraversion on English Language Oral Proficiency (ELOP) of the ESL Students at Tertiary Level of Education in Pakistan - Rehmat Ali, Rehmat Ali Yousaf Zai (Colombian Applied Linguistics Journal, 2025)
Broadly speaking, personality refers to the combination of traits that make people appear different and accordingly behave differently (Fazeli, 2012; Yusoff, Rahim, & Esa, 2010; Wakamoto, 2000; Ehrman & Oxford, 1990). Based on this psychological endowment, individuals shall either be introverts or extroverts while behaving during oral discourses (Sharma, 2008). This study investigates the impact of personality on English language oral performance (ELOP), focusing on accuracy, fluency, and vocabulary. A purposive sample of 35 tertiary-level students was selected. Two personality measuring scales, i.e. Eysenic Personality Inventory (EPI) and the Myers-Briggs Type Indicator (MBTI), were used to determine the specific traits of the participants. On the basis of the score obtained, the participants were classified as introverts and extroverts. Classroom observations, guided by observational protocols, were conducted in gleaning data. To minimize researcher bias, observations were conducted collaboratively with co-researchers and their observation and further followed by validation through concerned class teachers. Thematic analysis of the collected data revealed that extraversion significantly influences ELOP.